2012
DOI: 10.1159/000337590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc and DHA on the Epigenetic Regulation of Human Neuronal Cells

Abstract: Dietary intake of zinc and omega-3 fatty acids (DHA) have health benefits for a number of human diseases. However, the molecular basis of these health benefits remains unclear. Recently, we reported that zinc and DHA affect expression levels of histones H3 and H4 in human neuronal M17 cells. Here, using immunoblotting and densitometric analysis, we aimed to investigate the effect of zinc and DHA on post-translational modifications of histone H3 in M17 cells. In response to increase in zinc concentration, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 57 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, during the zinc effect, caspase 3 expression increased, whereas Bcl-2 expression decreased. This observation was in complete contrast to the DHA effect, which demonstrates the highly neuroprotective properties that DHA offers in modulating the chromatin state and thus ameliorating the incidence of neurodegenerative diseases (25) . This research opens up new avenues to therapeutic potentials in treating neurodegenerative diseases such as AD.…”
Section: Epigenetic Mechanisms and Neuronal Protectionmentioning
confidence: 74%
See 3 more Smart Citations
“…Furthermore, during the zinc effect, caspase 3 expression increased, whereas Bcl-2 expression decreased. This observation was in complete contrast to the DHA effect, which demonstrates the highly neuroprotective properties that DHA offers in modulating the chromatin state and thus ameliorating the incidence of neurodegenerative diseases (25) . This research opens up new avenues to therapeutic potentials in treating neurodegenerative diseases such as AD.…”
Section: Epigenetic Mechanisms and Neuronal Protectionmentioning
confidence: 74%
“…The study effectively demonstrated that the DHA treatment induced H3K9 acetylation, including K9, K36, and K79 dimethylation, which decreased when treated with zinc. Alternatively, zinc promoted K4 and K27 dimethylation and T3 phosphorylation, which were shown to decrease upon DHA treatment (25) . This study provides insight into the underlying molecular mechanisms regarding dietary intake and its influence on epigenetic regulations, particularly histone PTMs in human neuronal cells.…”
Section: Epigenetics and Gene Expressionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, docosahexaenoic acid decreased expression of HDAC1, HDAC2, and HDAC3 and induced global histone changes associated with transcriptional activation including H3-lysine-9 acetylation enrichment as well as depletion of H3-lysine-9 and -27 dimethylation in human neuronal cells. 159 Interestingly, docosahexaenoic acid was also shown to increase expression of H3 and H4 histones in the same cell line. 160 By contrast, palmitate induced HAT activity, and several genes that were modulated by lipotoxicity displayed altered patterns of histone modification in clonal β-cells.…”
Section: Epigenetics Of Lipid Metabolismmentioning
confidence: 93%